2018
DOI: 10.31665/jfb.2018.2147
|View full text |Cite
|
Sign up to set email alerts
|

Wheat gliadin deamidated by cation-exchange resins induces oral tolerance in a mouse model of wheat allergy

Abstract: Wheat allergy is a serious disease because it is difficult to be outgrown and sometimes induces anaphylaxis. Gliadin, a major allergen in wheat, deamideted by cation-exchange resins (DG) had low allergenicity not only in vitro but also in vivo. As the allergen-specific immunotherapy, a treatment for allergies, hold a risk of severe allergic reaction, the deamidated gliadin that has low allergenicity would provide an effective tool for treatment of wheat allergy. Thus, we examined if DG would induce oral tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For example, Lactobacillus helveticus -fermented soy protein isolate showed up to 100% reduction in immunoglobulin E reactivity, while the fermentation induced by Lactobacillus plantarum strains decreased by 83.8–94.8% [ 133 ]. Chemical modification techniques through deamidation by cation-exchange resins could also decrease the oral allergenicity in vitro and in vivo of gliadin, a major allergen in wheat [ 134 ].…”
Section: Effects Of the Different Modification Approaches On Nutritional Quality Bioactivity And Techno-functionalities Of Plant-based Prmentioning
confidence: 99%
“…For example, Lactobacillus helveticus -fermented soy protein isolate showed up to 100% reduction in immunoglobulin E reactivity, while the fermentation induced by Lactobacillus plantarum strains decreased by 83.8–94.8% [ 133 ]. Chemical modification techniques through deamidation by cation-exchange resins could also decrease the oral allergenicity in vitro and in vivo of gliadin, a major allergen in wheat [ 134 ].…”
Section: Effects Of the Different Modification Approaches On Nutritional Quality Bioactivity And Techno-functionalities Of Plant-based Prmentioning
confidence: 99%
“…We have developed a technique to deamidate proteins without causing peptide-bond hydrolysis, using carboxylated cation-exchange resins [13][14][15]. We have also shown that the deamidation of glutamine resides is quite effective to reduce allergenicity of orally administered gliadin [16,17], and that oral administration of deamidated gliadin induces oral tolerance [18]. However, the mechanism of cutaneous sensitization to induce wheat allergy would be different from that of oral sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have reported that enzymatic hydrolysis and deamidation of gliadin could increase its solubility in water and reduce its allergenicity in regard to the IgE level [10]. Deamidation of gliadin using cation-exchange resins could induce oral tolerance, regardless of whether deamidated gliadin was applied before or after gliadin sensitization [10][11][12]. Enzymatic hydrolysis combined with acid deamidation has been shown to increase the solubility, foaming, and emulsifying properties of gluten [13].…”
mentioning
confidence: 99%